MOBILE APPLICATION DEVELOPMENT FOR CHRONIC DISEASES RECORDING OF ARMY MEMBERS - Haris, M Syauqi; Bagus Prasetyo Abdi , Benben; Teja Kusuma, Wahyu (Jurnal Mnemonic, 2025)
Health services for army personnel play a crucial role in supporting military readiness and national defense. However, the current chronic disease data collection for army members is still conducted manually, causing inefficiencies in updating health information and hindering prompt promotive and preventive actions. This situation highlights the urgency for an integrated and accessible information system that allows health officers to monitor chronic illness cases more efficiently, especially in supporting early interventions and reducing curative and rehabilitative workloads. This research presents the development of a Mobile Device Application designed specifically for chronic disease data recording among army members, implemented in the Brawijaya Military Regional Health Unit (Kesdam V Brawijaya). The application, which is an expansion of the previously developed RAPI (Realtime Accountable Professional Integrative) system, utilizes Progressive Web App (PWA) technology to ensure accessibility and flexibility for users. The development followed the System Development Life Cycle (SDLC) methodology, with features tailored to stakeholder requirements, such as data grouping, diagnosis tracking, check-up history, and real-time reporting. The testing phase showed valid results for all system functionalities and confirmed compatibility across various smartphone types. The application successfully met all functional specifications and user needs, enabling faster access to health data, supporting preventive action planning, and reducing delays in chronic disease treatment monitoring. In conclusion, this application offers an effective, user-friendly, and scalable solution to improve health service delivery and chronic disease management for military personnel